2015
DOI: 10.14583/2318-7670.v03n01a02
|View full text |Cite
|
Sign up to set email alerts
|

Densidade e Poder Calorífico como Base para Prevenção de Incêndios Florestais sob Linhas de Transmissão

Abstract: Indigofera suffruticosa Mill. em uma área de Cerrado, em Barreiras-BA, visando a prevenção de incêndios de grande intensidade. A densidade básica da madeira e o poder calorífico das espécies P. bracteosa, C. argirophylloides, C. leprosum, M. tenuiflora e L. auriculata, apresentaram os maiores valores, o que provavelmente fará com que as mesmas produzam energia suficiente para uma queima intensa, representando um risco de incêndios na área de Caatinga. No trecho de Cerrado as espécies S. paniculatum e P. reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
1
1
1
Order By: Relevance
“…The average value of basic density found was 0.64 g cm-3, classifying the studied wood as medium density wood, according to Melo, Coradin, and Mendes (1997). In a study by Machado Neto et al (2015), the authors found for Plathymenia reticulata Benth the average value of basic density of 0.52 g cm-3, showing to be lower than the average value found in the present work for the same species.…”
Section: Discussioncontrasting
confidence: 86%
“…The average value of basic density found was 0.64 g cm-3, classifying the studied wood as medium density wood, according to Melo, Coradin, and Mendes (1997). In a study by Machado Neto et al (2015), the authors found for Plathymenia reticulata Benth the average value of basic density of 0.52 g cm-3, showing to be lower than the average value found in the present work for the same species.…”
Section: Discussioncontrasting
confidence: 86%
“…A determinação do poder calorífico de espécies também é utilizada como um parâmetro para o manejo florestal, com intuito de prevenção ou diminuição de incêndios, visto adequar espécies para composição florestal (MACHADO NETO et al 2015).…”
Section: Resultados E Discussõesunclassified
“…Caatinga and Cerrado biomes are represented by seasonally dry tropical forests, composing one of the world's most endangered tropical biomes, with poorly known flora and severely threatened by multiple pressures (Miles et al, 2006;Fernandes et al, 2020). The number of studies focused on the plant communities and growth under transmission lines are small (Wagner et al, 2014;Li and Lin, 2019) and few studies have been found to date that address the question of what the appropriate forest restoration and management under powerlines in Brazilian biomes (Oliveira and Zaú, 1998;Xavier et al, 2007;Machado Neto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%